Odpowiedź :
Odpowiedź:
a)
[tex]6 - 1\frac{2}{5}=5-\frac{2}{5}=4\frac{3}{5}[/tex]
b)
[tex]7 - 4\frac{2}{9}=3-\frac{2}{9}=2\frac{7}{9}[/tex]
c)
[tex]6-3\frac{1}{11}=3-\frac{1}{11}=2\frac{10}{11}[/tex]
d)
[tex]8-2\frac{3}{7}=6-\frac{3}{7}=5\frac{4}{7}[/tex]
e)
[tex]6-1\frac{5}{9}=5-\frac{5}{9}=4\frac{4}{9}[/tex]
f)
[tex]10-5\frac{4}{11}=5-\frac{4}{11}=4\frac{7}{11}[/tex]
Szczegółowe wyjaśnienie:
Odpowiedź:
a ) 6 - 1 i 2/5= 5-2/5= 4 i 3/5
b) 7 - 4 i 2/9= 3-2/9= 2 i 7/9
c) 6- 3 i 1/11= 3- 1/11= 2 i 10/11
d) 8-2 i 3/7= 6- 3/7= 5 i 4/7
e) 6-1 i 5/9= 5- 5/9= 4 i 4/9
f) 10-5 i 4/11= 5- 4/11= 4 i 7/11
Szczegółowe wyjaśnienie: